New sustainability for the neighborhoods of the great Chilean metropolis - Arnet Callealta, Virginia; Naranjo Escudero, Enrique (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
The capacity of the great Chilean metropolis to notably support the changes derived from contemporary human activity, poses the opportunity to design a new methodology of sustainable evaluation that contributes to generate a compact and complex urban model that consolidates sustainable standards adapted to the neighborhood scale of Santiago de Chile. The research will be articulated based on the theoretical-conceptual positioning and review of the state of the sustainability issue and the instruments for its evaluation, and the design of a complex and totalizing evaluation system that will condition the study by incorporating quantitative and qualitative indicators. From the above, results will be derived that fit the new model, which considers the traditional dimensions of sustainability - environmental, social and economic - to redefine them under a paradigm shift that understands the urban environment as a complex system.